Analisis Implementasi Kurikulum Merdeka dalam Pembelajaran Matematika Siswa Kelas 1 Madrasah Ibtidaiyah Bojonegoro - Setyowati, Suci Yongki (Edu Journal Innovation in Learning and Education, 2024)
This research is to find out and examine "Analysis of the Implementation of the Independent Curriculum in Mathematics Learning for Madrasah Ibtidaiyah Bojonegoro Students. This type of research is qualitative research which looks and hears in closer and more detailed explanations and individual understanding of their experiences. The research was carried out at MI Mafatihul Huda Bojonegoro . The population used was grade 1 students at MI Mafatihul Huda Bojonegoro. The research instrument was a questionnaire regarding the application of the Independent Learning Curriculum to mathematics subjects The overall aspect of the independent learning curriculum applied to grade 1 students at MI Mafatihul Huda is said to be high with a percentage of knowledge aspects of counting, counting and the profile of strengthening Pancasila of 80%. Utilization and retrieval aspects of 75%. The counting and counting skills aspect is 78%.